Is Upper Pole Puncture for Percutaneous Nephrolithotomy (PCNL) Safe and Effective? - Irfan Sharif; Irfan Sharif; Athar Mahmood; Ghulam Ghous; Nabeel Shafi; Humayun Saeed; Muhammad Shahzad Anwar; Muhammad Farooq (Proceedings, 2021)
Introduction: During this modern era of surgery, where miniaturization has taken a front row seat, endo-urology is flourishing like never before. PCNL has become the chosen tool for treating Staghorn stones, large renal calculi and complex upper ureteric calculi. The renal collecting system can be accessed by upper or lower pole puncture. Lower pole access is considered safer with fewer complications; however the benefits of upper pole access for PCNL also stands tall due to direct access to the most of renal calyxes system, renal pelvis and upper ureter. A lot of debate and confusion is recorded worldwide with respect to both methods.